Residential interior design a guide to planning spaces - Mitton, Maureen; Nystuen, Courtney; Brewer, Melissa; Pecha, Shelley; Bowe, Jamey (Hoboken, New Jersey : John Wiley & Sons, Inc., 2022)
In the newly revised Fourth Edition of Residential Interior Design: A Guide to Planning Spaces, an accomplished team of design professionals delivers the gold standard in practical, human-centered residential interior design. Authors Maureen Mitton and Courtney Nystuen explore every critical component of interior architecture from the perspective of ergonomics and daily use. The text functions as a guide for interior design students and early-career professionals seeking a handbook for the design of livable, functional, and beautiful spaces. It includes hundreds of drawings and photographs that illustrate key concepts in interior design, as well as room-by-room coverage of applicable building codes and sustainability standards. The authors also cover all-new applications of smart building technology and updated residential building codes and accessibility standards
Introduction -- Basic design graphics and sample project -- Entrances and circulation spaces -- Social and leisure spaces -- Kitchens -- Bedrooms -- Bathrooms -- Utility and work spaces -- Sample project and related drawings -- Basic light frame residential construction -- Notes on remodeling -- Appendices
Includes bibliographical references (pages 265-266), appendices and index
Keywords: Interior architecture .; Dwellings -- Specifications .; Dwellings -- Planning .; Interior Design and Furnishings